Implementasi UI/UX Pada Perancangan Sistem Informasi Konsultasi Klinik Menggunakan Metode Design Thinking - Lufiani, Tias; Suratno, Tri; Fadhila Putri, Mutia (JURNAL FASILKOM, 2026)
Access to healthcare services at Klinik Pratama Dokter Yanti is still constrained by distance, time, and long waiting queues. In addition, the clinic has not yet implemented telemedicine services, highlighting the need for an information system to improve accessibility and efficiency. This study aims to design a user interface and user experience (UI/UX) for a clinical information system that supports telemedicine features. The approach used is Design Thinking, with its five key stages: empathize, define, ideate, prototype, and test, as it emphasizes problem-solving based on user needs. Data were collected through interviews and observations involving patients or individuals who have interacted with the clinic to identify user needs and issues. The outcome is a web-based UI/UX prototype that includes an online consultation feature. Usability testing was conducted using the Maze platform with six respondents, resulting in Maze Usability Scores of 96, 90, and 94, indicating a high level of usability. In conclusion, the Design Thinking approach produces a system that is user-friendly, efficient, and aligns with user needs. Therefore, the proposed system is expected to address service accessibility challenges and enhance the quality of healthcare services at the clinic.